New frontiers of leadership - Graen, George B. (Emerald Publishing Limited : Information Age Pub., 2004)
This installment in the book series "LMX Leadership", edited by George B. Graen, focuses on New Frontiers of Leadership.
Keywords: Leadership.; Management.; Business & Economics -- Leadership.; Management: leadership and motivation.; elektronické knihy; electronic books